Are we hardwired - "Clark, William R." (Oxford, 2004)
Addressing one of the most controversial topics in human biology, the role of genes in governing behaviour, this book is sure to generate widespread interest. Clark and Grunstein are excellent guides to the current scientific understanding, explaining the genetic and molecular basis of human behaviour within the broader context of animal behaviour generally. They develop the subject clearly, building up from the classic twin studies in humans, and from the most basic behaviours such as chemotaxis in paramecia, to corresponding tropisms and memory in roundworms, and memory and learning in fruit flies, then to complex behaviours of mice and humans. They cover all of the politically sensitive issues of behaviour genetics as applied to humans - susceptibilities to disease, eating disorders, aggression, addiction and compulsive behaviours, intelligence, sexual orientation - clearly, and with impeccable balance. The authors show why they feel that substantial parts of our personalities and identities are established by our exact genetic complements, without reducing us to powerless creations our genes. Behaviour is treated as a complex interaction of nature and nurture - to understand ourselves fully, neither can be dismissed out of hand. Clark brings a fine balance and graceful touch to his most ambitious popular book yet.
Keywords: Behavior genetics